2008
DOI: 10.1016/j.jecp.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal provision of structure in a deliberate memory task in relation to their preschool children’s recall

Abstract: Strategic remembering emerges gradually during the preschool years. Socialization practices, specifically mother-child social interactions, might provide the foundation for developing of skills necessary for effective organization of information in memory. In the present study, 48 mothers and their 40-month-old children were engaged in the process of remembering (i.e., study and recall) categorically related picture stimuli in a laboratory context. Children's recall was reliably predicted by the way mothers st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…Indeed, Larkina, Güler, Bauer and colleagues have reported that mothers do differ in their use of memory strategies during a mother-child collaborative deliberate memory task and that these differences relate to children’s recall in the collaborative task and to children’s performance in individual deliberate memory tasks over time (see Larkina, Güler, Kleinknecht, & Bauer, 2008; Güler, Larkina, Kleinknecht, & Bauer, 2010). Future research could profitably examine the possible associations between the ways in which mothers reminisce with their children and also help their children deliberately “work to remember” information.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Larkina, Güler, Bauer and colleagues have reported that mothers do differ in their use of memory strategies during a mother-child collaborative deliberate memory task and that these differences relate to children’s recall in the collaborative task and to children’s performance in individual deliberate memory tasks over time (see Larkina, Güler, Kleinknecht, & Bauer, 2008; Güler, Larkina, Kleinknecht, & Bauer, 2010). Future research could profitably examine the possible associations between the ways in which mothers reminisce with their children and also help their children deliberately “work to remember” information.…”
Section: Discussionmentioning
confidence: 99%
“…The activities were substantially more personally relevant than those often undertaken in research on the development of episodic memory, such as studying and remembering a list of words or pictures (e.g., Güler, Larkina, Kleinknecht, & Bauer, 2010; Larkina, Güler, Kleinknecht, & Bauer, 2008). Yet they cannot be said to rise to the level of significance of the birth of a sibling, welcoming of a new puppy into the family, or losing a grandparent.…”
Section: Discussionmentioning
confidence: 99%
“…Há dois estilos de conversa das mães com seus filhos: as conversas mais elaboradas, que falam sobre o passado, e as menos elaboradas, que falam menos sobre o passado e não têm tanta riqueza de detalhes (Han, Leichtman, & Wang, 1998;Larkina, Güler, Kleinknecht, & Bauer, 2008); há ainda aquelas que falam sobre o futuro . Dessa forma, vão se formando os conceitos temporais da criança, assim como aqueles sobre si e sobre os outros .…”
Section: Desenvolvimento Da Memória: Da Primeira à Segunda Infância unclassified
“…A criança cuja mãe organiza seu discurso em categorias é mais propensa a ter melhor codificação e evocação de informações (Larkina et al, 2008). Observa-se que, em geral, meninas apresentam maior elaboração no diálogo com o pai aos 3, 6, 5 e 10 anos.…”
Section: Desenvolvimento Da Memória: Da Primeira à Segunda Infância unclassified